Ordboksomtale i Norge, især avisomtale - Guttu, Tor (LexicoNordica, 2004)
The article deals with the reviewing of lexicographic works in Norway, especially in newspapers. It states the facts that dictionaries seil poorly and that newspaper reviews are generally rare. Then it points to certain features in the reviews of the most important dictionaries and some other works from 1850 until today - features which to some extent can be seen as consequences of the Norwegian language situation. Finally, it is mentioned what can be done to direct attention to dictionaries and getting them more used in schools.